2014
DOI: 10.2754/avb201483040305
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of agmatine in acute chlorpromazine hepatotoxicity in rats

Abstract: The present study focused on potentially beneficial effects of agmatine on oxidative stress development in the liver during chlorpromazine treatment in rats. We wanted to examine the role of reactive oxygen species and efficiency of antioxidant protection through the determination of malondylaldehyde and total glutathione concentrations in rat liver homogenate, as well as plasma concentrations of malonylaldehyde and sulfhydryl groups after the treatment. Also, liver tissue sections were examined to follow hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
(9 reference statements)
2
4
0
1
Order By: Relevance
“…These results are in accordance with the previous reports suggested that SIL possess antioxidant, antiapoptotic, anti-inflammatory and immunomodulatory properties (Al-Rasheed et al, 2015Fraschini et al, 2002;Karimi et al, 2011;Pradeep et al, 2007). The hepatoprotective role of SIL was suggested to be due to its enhancement of CYP2E1 activity which has a major role in drug metabolism (Dejanovic et al, 2014;Jorgačević et al, 2014;Mahli et al, 2015;Wong et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in accordance with the previous reports suggested that SIL possess antioxidant, antiapoptotic, anti-inflammatory and immunomodulatory properties (Al-Rasheed et al, 2015Fraschini et al, 2002;Karimi et al, 2011;Pradeep et al, 2007). The hepatoprotective role of SIL was suggested to be due to its enhancement of CYP2E1 activity which has a major role in drug metabolism (Dejanovic et al, 2014;Jorgačević et al, 2014;Mahli et al, 2015;Wong et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…This metabolic process leads to the formation of reactive metabolites which bind to proteins and alter their function, leading to the loss of the catalytic activity of enzymes (Schiff et al 2007). Previous reports also suggested that CPZ increased free radicals generation and disturbed the hepatic and renal antioxidant enzymes activities (Dejanovic et al, 2014;Xu et al, 2010). It is well documented that oxidative stress in an organ is resulted from the increase production of reactive oxygen species (ROS) and the decline of the defense system due to the reduction of antioxidant enzymes activity (Abdel-Wahhab et al, 2016;Ostojić et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Očigledno je da AGM pokazuje protektivne efekte u odnosu na ćelijsku membranu samo u prisustvu oksidativnog stresa, u ovom slučaju izazvanog HPZ. To bi ukazivalo da se aktivacija procesa peroksidacije kod primene AGM ne odvija preko NO, već preko drugog mogućeg puta, a to je formiranje OH Uloga glutationa u zaštiti ćelija od toksičnih dejstava SR i drugih komponenata sa elektrofilnim svojstvima ogleda se u njegovom antioksidativnom dejstvu, jer neutrališe RVK unutar ćelije direktno ili preko ciklusa GPx/glutation (50,51). Povećanje nivoa ukupnog glutationa u kori prednjeg mozga 24 h posle trovanja HPZ je, uzevši u obzir njegovo antioksidativno dejstvo, rezultat aktivacije protektivnih mehanizama moždanog tkiva u ovim uslovima (Slika 3A).…”
Section: Diskusijaunclassified
“…Our previous study showed that CPZ increases the production of free radicals and affects the antioxidant enzyme activity in the rat liver [ 12 ]. It is known that OS in the liver is a consequence of increased production of free radicals and decreased capacity of antioxidant defense systems in hepatocytes [ 41 ].…”
Section: Introductionmentioning
confidence: 99%